Об отождествлении источников проложных поучений (на примере слова Анастасия Синаита о безгневии) - Паплаускайте, Вилия (Slavistica Vilnensis, 2010)
Anastasius Sinaita’s Homily on Peacefulness is attested in manuscript and printed copies of the Old Church Slavonic Synaxarion where it is read on both September 6 (The Wróblewskie Library of the Lithuanian Academy of Sciences, F 19, Nr. 95, 96) and March 19 (The Wróblewskie Library of the Lithuanian Academy of Sciences, F 19, 98, 99; the printed editions of 1660, 1856). While trying to identify the source of this particular sermon, I came across analogous texts in five different Old Church Slavonic books as follows: Izmaragd, Pandects by Nicon of the Black Mountain, Zlatoust, Zlataja Cep’, and Kievan Caves Patericon. As revealed by a word-byword comparison of the entire text of the synaxarion sermon with all the potential sources mentioned above, the synaxarion sermon exhibits the closest textual relation to the version of Izmaragd (chapter 17).